Physicochemical and microbiological analysis of stingless bees honey collected from local market in malaysia - W. N. Julika, .; Azilah, Ajit; Ahmad Ziad, Sulaiman; Aishath, Naila (Universiti Malaysia Pahang, 2018)
Honey is a sweet, viscous solution containing approximately 200 compounds, with the major content being water and sugars [1]. Due to its high nutritional value and unique taste, honey became popular as natural sweetener and medicine [2]. The growing demand for honey in the market has led to the occurrence of the tampering honey with foreign substances and increases the production of artificial honey. Thus, the study aimed to assess the quality of purely harvested honey and commercial honey available in Malaysia market with respect to the physicochemical properties and microbial profile. Six samples of stingless bees honey collected from local market in Malaysia (Fig.1) were investigated. Physicochemical parameters such as pH, free acidity, moisture content, electrical conductivity, ash content, hydroxymethylfurfural (HMF) and diastase activity were analyzed in each honey samples.